Charlie and the great glass elevator - Dahl, Roald; Blake, Quentin (New York : Puffin Books, 2007)
Taking up where Charlie and the Chocolate Factory leaves off, Charlie, his family, and Mr. Wonka find themselves launched into space in the great glass elevator.
720
Accelerated Reader AR
Keywords: Science fiction; Humorous stories; Outer space -- Fiction